Results of Lateral Retinacular Release Plus Circumpatellar Electrocautery in Total Knee Arthroplasty without Patellar Resurfacing - Wang, Yong; Sun, Jun-Ying; Zha, Guo-Chun (The Journal of Knee Surgery, 2017)
Anterior knee pain (AKP) is integral to the overall success of total knee arthroplasty (TKA) without patellar resurfacing. Numerous studies have evaluated various factors that may contribute to AKP, including patellofemoral design, surgical technique, characteristics of the patient, and degree of chondromalacia. This study aims to explore whether patients who received lateral retinacular release (LRR) plus circumpatellar electrocautery (CE) in TKA attain a low incidence of AKP and whether the LRR plus CE increases postoperative complications. Between February 2001 and February 2009, all patients undergoing TKA without patellar resurfacing and LRR plus CE were evaluated. In total, 286 TKAs in 259 (88.7%) patients were available for assessment, with a mean of 9.3 ± 2.5 years (range: 6–14 years) after the index TKA. The patients were evaluated with a VAS and the Kujala patellofemoral score (KPS) for AKP and the Knee Society's clinical scoring system (KSS) for the clinical function. Satisfaction and LRR-related complications were also assessed. The mean KPS and KSS improved from 45.2 ± 12.9 and 75.4 ± 26.8 points preoperatively to 82.8 ± 10.0 and 151.6 ± 17.3 points at the final follow-up (p < 0.001), respectively. Subjectively, 5.6% (16 of 286) of patients suffered from AKP and 88.1% (252 of 286) were satisfied or very satisfied. Postoperative complications occurred in 15 (5.2%) patients, but these complications were mild and did not require reoperation. None of patients exhibited aseptic and septic prosthesis loosening and required revision surgery in the final follow-up. LRR plus CE appears to be a reasonable option in TKA without patellar resurfacing. It may achieve adequate mid-term results, with a low incidence of AKP and postoperative complications.The level of evidence of the study is therapeutic level IV.
Keywords: knee; patellar non-resurfacing; lateral retinacular release; circumpatellar electrocautery; anterior knee pain